Os Critérios para configuração de dano moral por abandono afetivo na relação paterno-filial segundo o entendimento do Superior Tribunal de Justiça - PAIXÃO, Gustavo Oliveira da (2022)
Considering the fact that affective abandonment has been an increasingly present theme in legal discussions and that it has become of great relevance in family law, since it directly affects fundamental rights of children and adolescents, subjects of developing law, it is important research on the criteria that the Superior Court of Justice used to characterize moral damage resulting from affective abandonment in the paternal-filial relationship, in order to bring to light how the jurisprudence of the STJ has been treating the issue. For that, it is necessary to research the jurisprudence and make them dialogue with the doctrine. Then, a bibliographic and jurisprudential research is carried out, which uses the hypothetical deductive method so, based on the STJ's doctrine and jurisprudential decisions, it is possible to understand the judges' comprehension of the present theme. In view of this, it appears that the Brazilian doctrine, for the most part, recognizes the possibility of parents' civil liability in the face of their children's emotional abandonment. The STJ's jurisprudence, however, is not peaceful in relation to the theme, however, in the decision in which it recognizes the moral damage resulting from emotional abandonment, it is possible to observe that the STJ started to recognize the relevance of the principle of affectivity and its relationship with the duty of care, in the search for the State to protect the best interests of children and adolescents.